The Impact of Project-Based Learning on Students' Science Literacy and Environmental Awareness: A Comprehensive Review - Bambang Kulup Karnoto; Dwiyanto Dwiyanto; Muhammad Arsyad (Journal of Pedagogi, 2025)
Project-Based Learning (PjBL) has emerged as a transformative pedagogical approach that significantly enhances students' science literacy and environmental awareness across various educational levels. This comprehensive review synthesizes evidence from 20 empirical studies and systematic reviews conducted primarily in Indonesia between 2020 and 2025, examining the effectiveness of PjBL in developing scientific competencies and environmental consciousness. The findings consistently demonstrate that PjBL significantly improves students' science literacy scores, critical thinking abilities, problem-solving skills, and conceptual understanding compared to conventional teaching methods. Furthermore, PjBL effectively cultivates environmental awareness, pro-environmental attitudes, and action-taking behaviors among students through engagement with authentic environmental issues. The review identifies key success factors including active student involvement, integration of higher-order thinking skills, real-world problem contextualization, collaborative learning environments, and technology integration. This study reveals that PjBL effectiveness is enhanced when integrated with STEM approaches, digital storytelling, multiliteracy pedagogies, and character education. The evidence supports PjBL as a highly effective instructional model for fostering 21st-century competencies, scientific literacy, and environmental stewardship in contemporary education systems.